921 Falling TVS: is it a resolved problem?. (1st September 2016) - Pietrantonio, V; Omizzolo, L; Snenghi, R; Spagna, A; Mazloum, R El; Vettore, G; Vigolo, S; Gaudio, RM; Feltracco, P; Barbieri, S
Abstract : Introduction: A growing number of injuries and deaths from televisions falling from furniture are reported in literature although these are completely preventable injuries. Such injuries are ideal for a public education campaign targeting parents, health care workers, and television manufacturers. Methods: We report 2 cases of trauma sustained from falling TV arrived to our Emergency Department. Results: In these 2 cases there are no adult witnesses to the event, but they were alerted by a loud crashing sound of a falling TV. The death incidents occurred because TVs were on surfaces not suitable for TVs, a bookcase in the first case, and in the second case on a small table. The Glasgow Coma Scale score on admission was 3, in the first case and 8 in the second. The first baby, 2 years old, reported major traumatic brain injuries, and the impact force resulted in severe trauma and death. CT results revealed extended fracture parietal-occipital. In the second case the baby was playing with the TV's electrical cords and remained blocked under the product resulting in crushing and compressing injuries: the entire dresser and television fell over and the television landed on the boy's head. Discussion: The kind of trauma sustained from a falling TV depends on the length of time the victim has been trapped under the TV, on the impact force, on the point where the victims were hit on the age, and on the weight and size of the TV. Conclusion: As the incidents resulted from the instability of the furniture on which the TVs were set and that the same TV's were not properly anchored and could fall onto the victims, it is to be noted that they can be prevented by simply anchoring TVs and furniture. Televisions should only be placed on furniture designed to hold them, such as stands or media centres or they should be anchored to the wall. Items that might tempt kids to climb should also be removed, such as toys and remote controls, from the top of the TV and furniture.